2019
DOI: 10.1186/s12955-019-1119-8
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and resilience of mothers and fathers with respect to the neurobehavioral performance of small-for-gestational-age newborns

Abstract: Background The existence of psychological distress (PD) during pregnancy is well established. Nevertheless, few studies have analyzed the PD and resilience of mothers and fathers during high-risk pregnancy. This study analyzes the differences between parents’ PD and resilience and the relation between them and the neurobehavioral performance of their SGA newborns. Methods This prospective study compares two groups of parents and newborns: case group (52 parents and 26 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 60 publications
(66 reference statements)
2
17
1
3
Order By: Relevance
“…Second, embedding this RCT in a prospective cohort study provides an excellent opportunity to examine trajectories of mental resilience factors and levels of peripartum depressive symptomatology in association with several maternal and child outcomes. To date, associations between resilience and psychological well-being have only been examined in non-pregnant populations, and associations between resilience factors and maternal or child outcomes have only been assessed in a few small-scale (longitudinal) studies [ 14 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, embedding this RCT in a prospective cohort study provides an excellent opportunity to examine trajectories of mental resilience factors and levels of peripartum depressive symptomatology in association with several maternal and child outcomes. To date, associations between resilience and psychological well-being have only been examined in non-pregnant populations, and associations between resilience factors and maternal or child outcomes have only been assessed in a few small-scale (longitudinal) studies [ 14 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In non-pregnant populations, positive associations between resilience and psychological well-being have been observed [ 12 ]. To date, only a few small studies have examined associations between levels of resilience (or related factors) and maternal depression and depressive symptoms or infant behavioral and developmental outcomes [ 14 16 ]. More specifically, by examining trajectories of antepartum and postpartum depressive symptoms in association with maternal antepartum resilience, psychological well-being, and developmental outcomes of the young child, a better understanding of individualized treatment options can be gained.…”
Section: Introductionmentioning
confidence: 99%
“…A 'normal pregnancy' can have a negative psychological impact on both the mother and her partner; however, this impact is exacerbated when the pregnancy is high-risk (7). In both instances, the focus tends to be on the impact on the mother's well-being and less so on the father's (8,9). This is particularly evident in some developed countries for example, where there are not only physical services for women that have a HRP (for pregnancy appointments; provision of food and other supplies etc.…”
Section: Background To the Studymentioning
confidence: 99%
“…Resilience could help individuals adopt positive coping strategies (disclosure and seeking support) to maintain good psychosocial function (34). Higher levels of resilience are reportedly associated with fewer negative emotions and better interpersonal communication (15,16,50). In terms of neuro mechanisms, resilience could invoke specific brain structures and neural circuits, prompting the individual to regulate emotion and engage in prosocial behavior (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…QOL among patients with IBD may be influenced by disease symptoms, treatment regimen, and various psychosocial variables (14). Psychosocial variables could affect the patients' psychological and social functions and alter gastrointestinal physiology by activating the microbiota-brain-gut axis, leading to decreased or improved QOL (15)(16)(17)(18). Sweeney and her colleagues reported that depression, fear avoidance, and catastrophizing were risk factors for IBD -related pain, while self-efficacy and mental well-being were protective factors (19).…”
Section: Introductionmentioning
confidence: 99%